2017
DOI: 10.1093/schbul/sbx150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Niacin-Blunted Subgroup of Schizophrenia Patients from Mood Disorders and Healthy Individuals in Chinese Population

Abstract: Schizophrenia (SZ) is a devastating mental disease caused by complex genetic and environmental factors. The pathological process and clinical manifestation of SZ are heterogeneous among patients, which hampers precise diagnosis and treatment of the disease. Since no objective marker for SZ has been established today, to identify a subgroup of the patients with homogeneous biochemical traits will provide a new angle for both researchers and clinicians to understand and manage the disease. In this study, we empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
3
17
0
2
Order By: Relevance
“…An independent sample group was recruited for the niacin-skin flushing test and genotyping of PLA2G4A and PTGS2. All individuals in this sample group have undergone the niacin-skin test according to our previously reported method and the 16-points total scores were calculated to indicate the degree of flushing [19] . The tagSNPs were identified using the CHB and CHS data in 1,000 genome database (phase 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent sample group was recruited for the niacin-skin flushing test and genotyping of PLA2G4A and PTGS2. All individuals in this sample group have undergone the niacin-skin test according to our previously reported method and the 16-points total scores were calculated to indicate the degree of flushing [19] . The tagSNPs were identified using the CHB and CHS data in 1,000 genome database (phase 3).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the PLA2/COX pathway is involved in the niacin skin flush reaction. Skin flushing in response to niacin is abnormally blunted among a subset of patients with schizophrenia and is considered a potential marker for schizophrenia [18 , 19] . The biochemical basis of the niacin skin flush response is reasonably well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, almost 60% of participants had not taken the omega-3 supplement as required, and a secondary analysis that compared compliant versus non-compliant participants showed that the cumulative psychotic conversion rate within one year was significantly higher in the non-compliant group compared to the compliant group (14.8% vs. 4.7%; p < 0.001) [191]. Actually, the research on this topic is relatively scarce and has brought some debate on the most appropriate source of omega-3 supplementation between DHA (22:5 PUFA) and EPA (20:5 PUFA) [192], and on the heterogeneity of patients, as several studies suggest that only a subgroup of patients have lipid abnormalities [172,173,193,194].…”
Section: Omega-3 Supplementation At Different Stages Of Schizophreniamentioning
confidence: 99%
“…Le test à la niacine mesure donc indirectement la teneur en AA dans les membranes et la propension à la synthèse des prostaglandines, anti-inflammatoires. Un sous-groupe de patients souffrant de schizophrénie a une moindre sensibilité et réponse vasodilatatrice à la niacine [47]. Le mécanisme d'action de la niacine fait partie de la voie métabolique de l'AA (oméga-6) et une réponse faible au test à la niacine pourrait refléter un déficit en AGPI [48].…”
Section: Inflammation Et Stress Oxydatif Dans La Schizophrénie : Phospholipase A2 (Pla2) Niacine Et Acide Arachidonique (Aa)unclassified